Pengelolaan Media Sosial dalam Penyebaran Informasi Kegiatan Online Public Relations - Adiatama, Bagas; AS, Enjang; Cholidah, Lida Imelda (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2021)
This study aims to find out how the management of social media carried out by the Public Relations of KPPBC TMP Cikarang in disseminating information as a form of online public relations activities by referring to the four-step concept of public relations. The results of the study can be concluded that the management of social media in the dissemination of information carried out by the public relations of KPPBC TMP Cikarang is in accordance with the concept of four steps of public relations, namely first, the defining stage of public relations problems is carried out through situation analysis, media selection analysis and target target analysis. Second, the planning and programming stage is carried out by setting goals, creating content plans, choosing content, and assigning resources. Third, the stage of taking action and commucicating is carried out through discussion, dissemination of information and rapid response. Fourth, the evaluating stage of the program includes monitoring, seeing public responses, listening to suggestions from superiors and internal meetings.